Tax Governance in the Era of Pillar Two: Legal Certainty, Risk Management, and Strategic Responses in Indonesia - Listyawati, Ika; Nurlaela, Lina (Summa : Journal of Accounting and Tax, 2025)
This study investigates Indonesia’s implementation of a global minimum tax under PMK 136/2024, which aligns with the OECD’s Pillar Two framework. The regulation introduces a 15% minimum effective tax rate for multinational enterprises (MNEs), aiming to address tax base erosion and ensure fair cross border taxation. The primary objective of this research is to assess the compliance implications, strategic adjustments, and governance challenges faced by MNEs operating in Indonesia under this new regime. A qualitative methodology was employed, incorporating literature synthesis, comparative regulatory analysis, and thematic interpretation of professional insights and policy documentation. The study draws upon Indonesia’s regulatory structure, OECD guidance, and professional commentaries to evaluate legal certainty, compliance obligations, and strategic tax planning responses. Key findings reveal that the regulation significantly increases administrative burdens for MNEs, particularly in managing GloBE Information Returns, calculating jurisdictional effective tax rates, and reconciling data between reporting streams. Transitional provisions, such as safe harbours and SBIE carve outs, offer partial relief but require detailed governance. The study also highlights that egal ambiguities, such as differences in interpretation of SBIE and limited administrative capacity, pose compliance risks in the form of late GIR reporting, errors in ETR calculations, and potential fines during the transition phase. The study concludes that Indonesia’s adoption of global minimum tax standards marks a transformative step in international tax policy. While the regulation promotes alignment with global norms, its successful implementation hinges on regulatory clarity, digital infrastructure, and institutional readiness. The findings offer practical guidance for policymakers and corporate decision makers seeking to navigate complex international tax reforms.